Penyamaran Status Sosial dalam Pemanfaatan Beasiswa KIP-K - Kevin Rifqi Julian; Rosa Tedjabuwana (Wajah Hukum, 2025)
Misuse of the Kartu Indonesia Pintar Kuliah (KIP-K) scholarship through falsification of personal data by economically capable individuals is a crucial issue that is detrimental to the underprivileged. This study aims to analyze the factors causing falsification of KIP-K data, its social impact, and the legal basis that regulates it. This study uses a normative legal approach with a literature study based on laws and regulations, books, and scientific journals. The focus of the study is falsification of personal data in the Kartu Indonesia Pintar Kuliah (KIP-K) program, reviewed from the aspects of criminal law and educational principles. Data collection was carried out through a review of legal documents and related literature, with qualitative analysis to understand the motives, impacts, and criminal liability. The results of the study show that the weak criminal sanctions in the Regulation of the Minister of Education and Culture Number 10 of 2020 and the online registration system that is vulnerable to manipulation encourage misuse. As a result, underprivileged people lose access to higher education, widen social inequality, and damage public trust in government programs. Law enforcement through Law Number 27 of 2022 concerning Personal Data Protection and Law Number 11 of 2008 concerning Electronic Information and Transactions needs to be harmonized to provide a deterrent effect. This study also aims to improve the integration of national databases and artificial intelligence technology for data verification to ensure that KIP-K is on target.